2018
DOI: 10.3389/fmicb.2018.03021
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Fingerprinting of Salinispora From Atlantic Oceanic Islands

Abstract: Salinispora (Micromonosporaceae) is an obligate marine bacterium genus consisting of three species that share over 99% 16S rRNA identity. The genome and biosynthetic pathways of the members of this genus have been widely investigated due to their production of species-specific metabolites. However, despite the species’ high genetic similarity, site-specific secondary metabolic gene clusters have been found in Salinispora strains collected at different locations. Therefore, exploring the metabolic expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…Between 2007 and 2017, 177 new actinobacterial species belonging to 29 novel genera and three novel families were described (Subramani and Sipkema, 2019). The Gram-positive actinobacteria are a major chemically prolific source of bioactive metabolites with anticancer, antimicrobial, antiparasitic, anti-inflammatory, antibiofilm activities, and antifouling properties, among others (Prieto-Davó et al, 2016;Bauermeister et al, 2018Bauermeister et al, , 2019Cartuche et al, 2019Cartuche et al, , 2020Girão et al, 2019;Pereira et al, 2020). There are several marine-derived actinomycete metabolites described in the literature.…”
Section: Bacteria and Archaeamentioning
confidence: 99%
“…Between 2007 and 2017, 177 new actinobacterial species belonging to 29 novel genera and three novel families were described (Subramani and Sipkema, 2019). The Gram-positive actinobacteria are a major chemically prolific source of bioactive metabolites with anticancer, antimicrobial, antiparasitic, anti-inflammatory, antibiofilm activities, and antifouling properties, among others (Prieto-Davó et al, 2016;Bauermeister et al, 2018Bauermeister et al, , 2019Cartuche et al, 2019Cartuche et al, , 2020Girão et al, 2019;Pereira et al, 2020). There are several marine-derived actinomycete metabolites described in the literature.…”
Section: Bacteria and Archaeamentioning
confidence: 99%
“…Salinispora arenicola is considered a strict marine bacterium, whose ecological role and relevance is still largely unknown. However, S. arenicola has recently gathered considerable attention due to its high proportion of specialized metabolite biosynthetic genes with promising biotechnological potential (Amos et al, 2017;Bauermeister et al, 2018).…”
Section: Isolation and Identification Of Salinispora Spp As Coral-asmentioning
confidence: 99%
“…Following this hint, further studies then confirmed the occurrence of Salinispora sp. at the SPSPA [81], which was the first report of this genus in Brazilian waters, and compared the metabolomics profile of strictly marine actinobacteria Salinospora arenicola and S. pacifica among strains occurring in Brazilian and Portuguese islands [152]. By using the spectral library search from GNPS, the authors showed that S. arenicola strains isolated from Brazilian waters are able to produce the molecular families of staurosporine, desferrioxamine, rifamycin, ferroxamine, and saliniketal, typical compounds to the metabolome of S. arenicola.…”
Section: Further Accessing Brazilian Marine Environments: Studies Witmentioning
confidence: 99%
“…By using the spectral library search from GNPS, the authors showed that S. arenicola strains isolated from Brazilian waters are able to produce the molecular families of staurosporine, desferrioxamine, rifamycin, ferroxamine, and saliniketal, typical compounds to the metabolome of S. arenicola. Through inspection of the molecular networking, a new saliniketal analog with a difference of a methyl group was found [152].…”
Section: Further Accessing Brazilian Marine Environments: Studies Witmentioning
confidence: 99%